2022
DOI: 10.1063/5.0072124
|View full text |Cite
|
Sign up to set email alerts
|

Strain-tunable in-plane ferroelectricity and lateral tunnel junction in monolayer group-IV monochalcogenides

Abstract: 2D ferroelectric materials are promising for designing low-dimensional memory devices. Here, we explore strain-tunable ferroelectric properties of group-IV monochalcogenides MX (M=Ge, Sn; X=S, Se) and their potential application in lateral field tunnel junction devices. We find that these monolayers have in-plane ferroelectricity, with their ferroelectric parameters being on par with other known 2D ferroelectric materials. Among SnSe, SnS, GeSe, and GeS, we find that GeS has the best ferroelectric parameters f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Very recently, monolayer group-IV monochalcogenides MX (M = Ge, Sn; X = S, Se), monolayer SbN and mono-layer BiP thin films were found to be good robustness ferroelectric materials with room temperature less than transition temperature. [6][7][8][18][19][20] The in-plane spontaneous polarization of these monolayers is relatively larger compared to other 2D ferroelectric materials. Moreover, these monolayers have excellent thermoelectric properties as well as massive piezoelectricity.…”
Section: Introductionmentioning
confidence: 89%
“…Very recently, monolayer group-IV monochalcogenides MX (M = Ge, Sn; X = S, Se), monolayer SbN and mono-layer BiP thin films were found to be good robustness ferroelectric materials with room temperature less than transition temperature. [6][7][8][18][19][20] The in-plane spontaneous polarization of these monolayers is relatively larger compared to other 2D ferroelectric materials. Moreover, these monolayers have excellent thermoelectric properties as well as massive piezoelectricity.…”
Section: Introductionmentioning
confidence: 89%
“…97 The S-curve, illustrated in Figure 4d, captures the polarization dependence on the electric field, and it is determined by E = dG/dP. 13,98 The blue shaded region in Figure 4a and Figure 4d is the region of negative capacitance. The capacitance C is proportional to slope dP/dE.…”
Section: ■ Out-of-plane Ferroelectricity In Monolayer Crtementioning
confidence: 99%
“…Atomically thin 2D materials have attracted significant interest for diverse applications, including electronics, optoelectronics, energy storage, sensors, and catalysis. However, one challenging frontier has been the quest for intrinsic 2D magnets with high Curie temperatures that are suitable for room-temperature magnetic applications. Several 2D materials have been proposed so far, with both the intrinsic and extrinsic origin of magnetism. Among them, some of the 2D materials like CrI 3 , Cr 2 Ge 2 Te 6 , VSe 2 , and Fe 3 GeTe 2 have shown promise.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that strain can significantly modify the crystalline structure and phases of the material, i.e., inducing the phase transition 45 and impacting the direction and magnitude of the ferroelectric polarization. 46,47 In experiments, strain engineering has been regarded as an efficient strategy to modulate a material's electronic, 48 optical, 49 polarization, 50 and magnetic 51 properties. All of these demonstrate the urgency and importance of the investigation of the effect of strain on the FGT monolayer.…”
Section: +mentioning
confidence: 99%